Evolution of Complex Thallus Alga: Genome Sequencing of Saccharina japonica - Liu, Tao; Wang, Xumin; Wang, Guoliang; Jia, Shangang; Liu, Guiming; Shan, Guangle; Chi, Shan; Zhang, Jing; Yu, Yahui; Xue, Ting; Yu, Jun (Frontiers in Genetics, 2019)
Saccharina, as one of the most important brown algae (Phaeophyceae) with multicellular thallus, has a very remarkable evolutionary history, and globally account for most of economic marine aquaculture production worldwide. Here we present the 580.5 million base pair of genome sequence of Saccharina japonica, whose current assembly contains 35,725 protein-coding genes. In a comparative analysis with Ectocarpus silicilosus, the integrated virus sequence suggested the genome evolutionary footprints, which derived from their co-ancestry and experienced genomic arrangements. Furthermore, the gene expansion was found as the important strategy for functional evolution, especially ones related to extracelluar components, stress-related genes, and vanadium-dependent haloperoxidases, and we proposed a hypothesis that gene duplication events were the main driven force for the evolution history from multicellular filamentous algae to thallus algae. The sequenced Saccharina genome paves the way for further molecular studies and is useful for genome-assisted breeding of S. japonica and other related algae species.